Web Application Vulnerability Detection Using Hybrid String Matching Algorithm - J. Santhosh Kumar, B; Pujitha, Kankanala (International Journal of Engineering and Technology, 2018)
Application uses URL as contribution for Web Application Vulnerabilities recognition. if the length of URL is too long then it will consume more time to scan the URL (Ain Zubaidah et.al 2014).Existing system can notice the web pages but not overall web application. This application will test for URL of any length using String matching algorithm. To avoid XSS and CSRF and detect attacks that try to sidestep program upheld arrangements by white list and DOM sandboxing techniques (Elias Athanasopoulos et.al.2012). The web application incorporates a rundown of cryptographic hashes of legitimate (trusted) client side contents. In the event that there is a cryptographic hash for the content in the white list. On the off chance that the hash is discovered the content is viewed as trusted or not trusted. This application makes utilization of SHA-1 for making a message process. The web server stores reliable scripts inside div or span HTML components that are attribute as reliable. DOM sandboxing helps in identifying the script or code. Partitioning Program Symbols into Code and Non-code. This helps to identify any hidden code in trusted tag, which bypass web server. Scanning the website for detecting the injection locations and injecting the mischievous XSS assault vectors in such infusion focuses and check for these assaults in the helpless web application( Shashank Gupta et.al 2015).The proposed application improve the false negative rate.Â Â